Is Transparency to no avail? Committee Decision-making, Pre-meetings, and Credible Deals - Otto H. Swank; Bauke Visser (Tinbergen Institute, 2007)
Transparent decision-making processes are widely regarded as a prerequisite for the working of a representative democracy. It facilitates accountability, and citizens may suspect that decisions, if taken behind closed doors, do not promote their interests. Why else the secrecy? We provide a model of committee decision-making that explains the public's demand for transparency, and committee members' aversion to it. In line with case study evidence, we show how pressures to become transparent induce committee members to organize pre-meetings away from the public eye. Outcomes of pre-meetings are less determined, more anarchic, than those of formal meetings, but within bounds. We characterize feasible deals that are credible and will be endorsed in the formal meeting.
Keywords: D71; D72; D82; 330; Committee decision-making; reputational concerns; transparency; pre-meetings; deliberation; Gruppenentscheidung; Politische Entscheidung; Geheimhaltung; Informelle Gruppe; Öffentliches Interesse